Type I Interferons Induce T Regulatory 1 Responses and Restrict Humoral Immunity during Experimental Malaria. - Ryan A Zander; Jenna J Guthmiller; Amy C Graham; Rosemary L Pope; Bradly E Burke; Daniel J J Carr; Noah S Butler (PLoS Pathogens)
CD4 T cell-dependent antibody responses are essential for limiting Plasmodium parasite replication and the severity of malaria; however, the factors that regulate humoral immunity during highly inflammatory, Th1-biased systemic infections are poorly understood. Using genetic and biochemical approaches, we show that Plasmodium infection-induced type I interferons limit T follicular helper accumulation and constrain anti-malarial humoral immunity. Mechanistically we show that CD4 T cell-intrinsic type I interferon signaling induces T-bet and Blimp-1 expression, thereby promoting T regulatory 1 responses. We further show that the secreted effector cytokines of T regulatory 1 cells, IL-10 and IFN-γ, collaborate to restrict T follicular helper accumulation, limit parasite-specific antibody responses, and diminish parasite control. This circuit of interferon-mediated Blimp-1 induction is also operational during chronic virus infection and can occur independently of IL-2 signaling. Thus, type I interferon-mediated induction of Blimp-1 and subsequent expansion of T regulatory 1 cells represent generalizable features of systemic, inflammatory Th1-biased viral and parasitic infections that are associated with suppression of humoral immunity.